2012
DOI: 10.1105/tpc.111.089441
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Transcriptome of Barley Chloroplasts: Numerous Noncoding RNAs and the Dominating Role of the Plastid-Encoded RNA Polymerase    

Abstract: Gene expression in plastids of higher plants is dependent on two different transcription machineries, a plastid-encoded bacterial-type RNA polymerase (PEP) and a nuclear-encoded phage-type RNA polymerase (NEP), which recognize distinct types of promoters. The division of labor between PEP and NEP during plastid development and in mature chloroplasts is unclear due to a lack of comprehensive information on promoter usage. Here, we present a thorough investigation into the distribution of PEP and NEP promoters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
205
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(222 citation statements)
references
References 97 publications
15
205
0
Order By: Relevance
“…Meanwhile, another transcript initiation site, PrbcL-319, was detected only in spectinomycin-treated seedlings and not in green seedlings ( Figure 3A), suggesting that this transcription initiation site is NEP dependent. Recently, a rbcL NEP promoter was identified in barley (Hordeum vulgare) as well (Zhelyazkova et al, 2012). The usage of the PrbcL-179 and PrbcL-319 promoters did not differ between the wild type and rhon1-2, suggesting that the accumulation of rbcL polycistronic transcript in rhon1-2 is not related to rbcL promoter usage.…”
Section: Mutation Of Rhon1 Affects Transcriptional Termination Of Rbclmentioning
confidence: 99%
“…Meanwhile, another transcript initiation site, PrbcL-319, was detected only in spectinomycin-treated seedlings and not in green seedlings ( Figure 3A), suggesting that this transcription initiation site is NEP dependent. Recently, a rbcL NEP promoter was identified in barley (Hordeum vulgare) as well (Zhelyazkova et al, 2012). The usage of the PrbcL-179 and PrbcL-319 promoters did not differ between the wild type and rhon1-2, suggesting that the accumulation of rbcL polycistronic transcript in rhon1-2 is not related to rbcL promoter usage.…”
Section: Mutation Of Rhon1 Affects Transcriptional Termination Of Rbclmentioning
confidence: 99%
“…In addition, the accD (NEP-generated) transcript exhibits a reduction of editing extent at site 794 in rip1, which is unlike other NEP transcripts (SI Appendix, Table S2). More importantly, the current view that genes of photosystems I and II are completely dependent on PEP transcription and a few housekeeping genes, including the rpoB operon, are transcribed exclusively from NEP promoters has been recently challenged in a study of the barley chloroplast transcriptome (49). In this study, which included a PEP-lacking plastid mutant, Zhelyazkova et al (49) observed that most genes, including genes coding for photosynthesis proteins, have both NEP and PEP promoters.…”
Section: Discussionmentioning
confidence: 97%
“…These authors contrasted the w2 RNA phenotype with those of two other albino mutants (w1 and iojap) that had normal levels of chloroplast DNA but aberrant transcript populations. In hindsight, it is clear that the w1 and iojap RNA and DNA content are typical of mutants in the grasses that lack plastid ribosomes: the ribosome deficiency results in stereotypical changes in transcript patterns presumably caused by the loss of PEP and enhanced transcription by NEP (Williams and Barkan, 2003;Prikryl et al, 2008;Zhelyazkova et al, 2012b). The fact that the transcript populations in w2-Burnham mutants more closely resemble those in wild-type plants than those in mutants lacking plastid ribosomes is interesting, because plastid ribosome abundance is drastically reduced in v2-Burnham mutants.…”
Section: Discussionmentioning
confidence: 99%